Pragmatics meaning interpretation and verbatim rendering in adversarial legal systems court interpreting - Nur Amalia Sari (ACCENTIA: Journal of English Language and Education, 2022)
As a result of global movement, either by voluntary migration or forced displacement, interpreter-mediated court proceedings are becoming increasingly common. Most courts established interpreter’s codes of conduct, preferring verbatim rendering of litigants’ utterances, in anticipation of potential cultural bias and partiality. However, this code of conduct seems to fail to accommodate complicated legal and language realities in intercultural court proceedings. In adversarial legal systems, the presentation of evidences highly relies on the skillful language manipulation by the lawyers. In terms of refugee status determination, the ability to retell traumatic experience determined asylum seekers’ credibility. Communication breakdowns and failure to provide cultural context are amongst the downside of verbatim rendering, since speakers have to breakdown their confession into short sentences to be fully translated. On other hand, in offering context and preserving intention, interpreter might be tempted alter speakers’ original voice/style, including eliminating repetitions, hesitations and inexplicitness. Considering this, it is suggested that pragmatic meaning interpretation is utilized by taking more caution to preserving speakers’ original style. In doing so, sufficient training for interpreters and sufficient number of interpreters must be provided.